The complexation of neptunium(V) with fluoride at elevated temperatures: speciation and thermodynamics - Maiwald, Martin M.; Fellhauer, David; Skerencak-Frech, Andrej; Panak, Petra (Applied geochemistry, 2019)
The complexation of NpO2+ with fluoride is studied in aqueous solution using Vis/NIR absorption spectroscopy. The total ligand concentration (NaF), ionic strength (NaClO4), and temperature (T=20-85°C) is varied, yielding detailed information on the thermodynamics of the complexation reaction. Two distinct complex species (NpO2Fn1−n, n=1, 2) are identified by peak deconvolution of the absorption spectra. At 20°C and Im=1.0 the absorption band of NpO2F is located at 983.8±0.2nm. The absorption band of the NpO2F2− complex is located at 988.4±0.2nm. With increasing temperature and ionic strength the chemical equilibrium of the complexation reaction shifts towards the complexed Np(V) species. The conditional stability constants logβ‘n(T) are calculated according to the law of mass action and are extrapolated to Im=0 for each temperature with the specific ion interaction theory (SIT). The determined logβ0n(T) values increase by 0.2-0.6 in the studied temperature range. Furthermore, the logβ0n(T) values correlate linearly with the reciprocal temperature and fitting the data according to the integrated Van't Hoff equation yields the standard reaction enthalpies (ΔrH0m) and entropies (ΔrS0m). The reactions are endothermic and are solely driven by the high gain of entropy. In addition, the binary SIT ion-ion interaction coefficient εj,k of the respective complex species are determined.
Gesehen am 03.09.2019